How attachment and community identification affect user stickiness in social commerce: a consumer engagement experience perspective - Gao, Xian; Yee, Choy Leong; Choo, Wei Chong (Multidisciplinary Digital Publishing Institute, 2022)
Social commerce (s-commerce) is a rapidly developing form of e-commerce powered by social media influencers (SMIs). It can create valuable opportunities for retailers. In light of this growing trend, this study explores the influence of consumers’ engagement experiences (social support and presence) on community identification and consumers’ attachment to SMIs, along with their impact on consumers’ stickiness in the s-commerce context. We explore this through social presence and social support theory. The survey data from 411 s-commerce users via an online questionnaire were analyzed empirically with the PLS-SEM approach. The results indicated that presence and social support have significantly positive impacts on consumers’ attachment to SMIs and community identification, respectively. This increases users’ stickiness in s-commerce. This study enriches our understanding of user stickiness in s-commerce and can assist online vendors in developing marketing strategies and cultivating sustained relationships with their users.